PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV TEMA SELALU BERHEMAT ENERGI BERDASARKAN TAKSONOMI BLOOM - Kumala, Sinar; Khosiah, Nur; Atus Soliha, Imro (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research applies classroom action research (PTK) where the action process in implementing learning carries out two cycle stages, namely cycles (scale I and II). Each time it contains the process of preparation, implementation, observation and planning. The research subjects were 20 class IV students at MI Darus Sholihin for the 2022-2023 academic year. Furthermore, the aim of this research is that researchers want to find out whether the application of the jigsaw type learning model can provide a significant increase in changes in students' learning outcomes, teaching materials that always save energy and their use, science subjects. Then, to show curiosity about the results of students' learning achievements, a process of evaluating student learning outcomes based on Bloom's taxonomy is needed. From this review, it is clear that the implementation of the jigsaw type teaching model has experienced an improvement in each cycle, as evidenced by the previous cycle (period I) the students' learning scores only obtained an average of 64.95 with a percentage of 53% and in the cycle (period II) the average score was 80. 1 with a percentage of 94.73%, resulting in an increase in the average score of 15.15 (41.73) students who had completed and met the classification standards (criteria) determined by the researcher.